Diabetes and hypertension in urban bhutanese men and women - Bhakta Raj Giri; Krishna Prasad Sharma; Rup Narayan Chapagai; Dorji Palzom (Indian Journal of Community Medicine, 2013)
Background: Bhutan is a mountainous country with 31% urban population. There is no information on prevalence of diabetes and hypertension in Bhutan yet. This was the first study of its kind conducted in the capital city. Objective: To determine prevalence of diabetes, impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and hypertension in urban Bhutanese population aged 25 to 74 years. Materials and Methods: Stratified two-stage sampling was adopted to include 2474 respondents (Males: 1132, Females: 1342) equally distributed among different age and sex groups. A questionnaire containing demographic, educational and social details and history of diabetes and hypertension was administered on the sampled population the previous evening and blood pressure measured the next morning in nearby camp where fasting blood samples were collected and an oral glucose tolerance test done. Results: Age and sex standardized prevalence of diabetes, IGT and IFG were 8.2.0, 21.6 and 4%, respectively. Only 66.5% of the population had normal blood sugar. Prevalence of diabetes and IGT increased progressively with increasing age. Prevalence of hypertension was 26% (Males: 28.3%, Females: 23.2%). It was observed that 54.1% of diabetes population had hypertension. Conclusion: The study shows that not only is prevalence of diabetes and hypertension high in the urban Bhutanese but also there is a high diagnosis and treatment gap in these disorders.